Letramento crítico multimodal no ensino de língua portuguesa a partir de tiras - Santiago, Leiliane Nogueira (Universidade Federal Rural do Semi-Árido, 2020)
There are several ways in which language can be and is used to maintain and cope with forms of power (Janks, 2016), it‘s necessary to pay special attention to what is read on a daily basis, taking into account not only the verbal code, but all features semiotics that make up the texts, since multimodality is an intrinsic condition of human communication (KRESS, 2010).Therefore, this research aims to analyze the Multimodal Critical Literacy of High School students from comic strips. Specifically, seeking to understand how students identify and understand ideologically naturalized discourses from the verb-images elements of the comic strips, and seeking to analyze how students deconstruct the asymmetrical power relations represented in them. Therefore, the discussions developed about the notion of criticality and critical literacy are supported by the theoretical postulations of Street (2014), Silva, M. Z. V. (2016), Janks (2012, 2016), Freire (1981, 1987,1989, 1996) and, above all., in the theoretical contribution of Critical Discourse Analysis from the perspective of Fairclough (1989, 2001 2003), Chouliaraki and Fairclough (1999) and Resende and Ramalho (2006). In reference of the concepts of multi-measures, multimodality and multimodal literacy, the theoretical framework of the New London Group (1996), Cope and Kalantzis (2015), Rojo (2012), Dionísio (2011, 2013, 2014), Jewitt (2008), Hodge and Kress (1988), Kress (2003, 2010), Kress and van Leeuwen (2006),van Leeuwen (2017) and Predebon (2015).In meeting the goals set, a predominantly qualitative research was conducted through an action research (RICHARDSON, 2017), whose group of participants was composed of eight students of the 3rd year of High School of a public school of the state school system Ceará teaching. The research data were constituted through the answers collected by the pretest / posttest and the critical redesign activity performed during the classroom intervention process, in which they were explored in the light of Visual Design Grammar (KRESS; VAN LEUWEEN, 2006) and Critical Discourse Analysis, Armandinho's comic strips collected from his Facebook page. According to the results, it was found that students mobilize and articulate knowledge concerning these two theoretical contributions mentioned above, which contributed to the identification, comprehension and deconstruction of the ideological discourses that cross the texts. In particular, an improvement in comprehension capacity of the semiotic resources that compose the images, which possibly triggered a more satisfactory performance in the other aspects analyzed. In short, the interrelationship of this knowledge, viewed from a critical the broader construction / deconstruction / reconstruction, according to Janks (2012), contributed to catch and even collaborate with the Multimodal Critical Literacy of the research subjects
Keywords: Letramento crítico multimodal; Tiras; Ensino de Língua Portuguesa; Multimodal critical literacy; Comic strips; Portuguese Language Teaching; MULTIDISCIPLINAR::ENSINO